II-19 Elevated plasma cell-free mitochondrial DNA defines a subgroup of lupus patients with membranous lupus nephritis. (31st August 2016) - Fernandez, David R; Pabon, Maria A; Olferiev, Mikhail; Hernandez, Ana C; Malick, Faryal; Khalili, Leila; Nakahira, Kiichi; Choi, Augustine MK; Crow, Mary K
Abstract : Background: Systemic lupus erythematosus (SLE) is an autoimmune disease with protean manifestations, characterised by production of antibodies against nucleic acids and upregulation of type I interferon-inducible genes in a majority of SLE patients. The principal drivers of this interferon signature are still not well understood. Recent work has shown that oxidised mitochondrial DNA released by neutrophils can stimulate plasmacytoid dendritic cells to produce interferon-α. 1 We hypothesised that cell-free mitochondrial DNA might contribute to type I interferon production in SLE, and we sought to examine whether cell-free mtDNA levels were increased in SLE patients relative to controls, or during disease flares. Materials and methods: A retrospective analysis was performed using banked plasma samples from 164 patients in our SLE cohort along with 57 banked plasma samples from healthy donors. DNA was isolated from the plasma samples and real-time quantitative PCR was performed, amplifying a target sequence in the mitochondrially-encoded gene NADH dehydrogenase I, as previously published. 2 In-depth clinical phenotyping of SLE patients in the cohort was performed and used to define subgroups of SLE patients, as well as the specific disease manifestations present during flares. Results: No significant difference was seen in cell-free mtDNA in plasma from SLE patients versus healthy donors (HD – 3060.3 copies/uL, N = 57, SLE - 3845.5 copies/uL, N = 164, p = 0.22). However, cell-free mtDNA levels were elevated in a subset of SLE patients with a history of membranous lupus nephritis, including those with a component of proliferative nephritis (WHO class V/III+V/IV+V), relative to patients with proliferative nephritis alone (WHO class III or class IV) (5313.9 copies/uL, N = 34 vs. 2062.5 copies/uL, N = 17, p = 0.02). A subset of 70 patients had multiple samples collected at visits before, during, and after flares of disease activity. Cell-free mtDNA levels rose at the peak of disease activity as assessed by SLEDAI score in 11/16 flares of class V/III+V/IV+V nephritis (p = 0.04), while it only did so in 4/11 of the remaining nephritis flares. In contrast, cell-free mtDNA rose at the peak of disease activity in only 4/20 flares where alopecia was present (p = 0.02). Conclusions: Cell-free mtDNA levels are elevated in a subset of SLE patients with a history of membranous nephritis, and were more likely to rise during flares of membranous nephritis versus other types of disease flares. Acknowledgements: Supported by a Lupus and Antiphospholipid Centre of Excellence Research Fund Award References: Lood C, et al . Neutrophil extracellular traps enriched in oxidised mitochondrial DNA are interferogenic and contribute to lupus-like disease. Nat Med advance on, 2016 Nakahira K, et al . Circulating mitochondrial DNA in patients in the ICU as a marker of mortality: derivation and validation. PLoS Med 2013;10:e1001577; discussion e1001577